Rapid quantitative analysis of monoclonal antibody heavy and light chain charge heterogeneity - Vanam, Ram P (MAbs, 2015)
An alternative method to traditional 2-dimensional gel electrophoresis (2D-PAGE) and its application in characterizing the inherent charge heterogeneity of chromatographically isolated monoclonal antibody heavy and light chains is described. This method, referred to as ChromiCE, utilizes analytical size-exclusion chromatography (SEC), performed under reducing and denaturing conditions, followed by imaged capillary isoelectric focusing (icIEF) of the chromatographically separated heavy and light chains. Under conditions suitable for the subsequent icIEF analysis, the absolute and relative SEC elution volumes of the heavy and light chains were found to be highly pH dependent, a phenomenon that can be exploited in optimizing chromatographic separation. Compared to 2D-PAGE, the ChromiCE method substantially decreases the time and labor needed to complete the analysis, improves reproducibility, and provides fully quantitative assessment of charge heterogeneity. The ChromiCE methodology was applied to a set of diverse monoclonal antibodies to demonstrate suitability for quantitative charge variant analysis of heavy and light chains. A typical application of ChromiCE in extended characterization and stability studies of a purified antibody is shown.